If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) = 9 + -3x Reorder the terms: 2(-3 + x) = 9 + -3x (-3 * 2 + x * 2) = 9 + -3x (-6 + 2x) = 9 + -3x Solving -6 + 2x = 9 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -6 + 2x + 3x = 9 + -3x + 3x Combine like terms: 2x + 3x = 5x -6 + 5x = 9 + -3x + 3x Combine like terms: -3x + 3x = 0 -6 + 5x = 9 + 0 -6 + 5x = 9 Add '6' to each side of the equation. -6 + 6 + 5x = 9 + 6 Combine like terms: -6 + 6 = 0 0 + 5x = 9 + 6 5x = 9 + 6 Combine like terms: 9 + 6 = 15 5x = 15 Divide each side by '5'. x = 3 Simplifying x = 3
| 5+9= | | 3x^2+2x-144=0 | | x^4+4x^3-5x^2-16x+4=0 | | 2(-4y^2)= | | 38(12-4.5x)=12(4x-10)+28.5 | | 16m-9n+2m+11n= | | x(5x+19)=4 | | 4(d+5.2)=10d-6.2 | | 7x+6y=-2 | | 0=16t^2+3 | | k^2+9k+8=0 | | 6.5(y-5)=6.2-y | | 0=-16t^2+20t+3 | | 3(x+5)=9x-24 | | 5-n=7 | | 8(x+3)=5x+45 | | 12[z-7]=60 | | 3k^2+25k+8=0 | | 2.4x+67=3.9x+25 | | 16m-9n+2m+11m= | | (x+8)(9x+11)=0 | | 16x^2-4x-20=0 | | x^2-1x+5=0 | | 4(x-1)-4=0 | | 2.4x+6.7=3.9x+25 | | -43+2y+3=2(3y-4)-4 | | 12x^2+11x+2=0 | | -6(5x+4)= | | 9x+17-8x=-6-12 | | 5y-5=16+10y | | 16x^2-16x-5=0 | | -4x+1+5x=-4+9 |